PENGARUH JOB DESCRIPTION DAN DISIPLIN TERHADAP KINERJA KARYAWAN PT KINCO PRIMA: english - Susanti Gea, Dewi; Khoiri, M. (LPPM Universitas Putera Batam, 2022)
This study aims to analyze the effect of job description and discipline on employeeperformance at PT Kinco Prima. Used a type of research with a population of 106 people.Used a questionnaire for data collection. The sampling technique used is the saturatedsample, meaning that all the population is sampled. The data is processed using SPSSversion 26 with the results of the study it is known that Job Description has a arithmeticvalue > t table that is 6.486 > 1.98326 with a significance of 0.000 < 0.05 which means thatthe quality of the Job Description product has a positive and significant effect on employeeperformance, t arithmetic discipline is known. > t table that is 6.709 > 1.98326 with asignificance of 0.000 <0.05 which means that discipline has a positive and significant effecton employee performance. And Job Description and discipline together have a positiveand significant effect on employee performance. This is evidenced by the results of the Ftest with a value of (F count) 99.898> 3.08 (F table) with a significance value of 0.000<0.05. And R square value is 0.660.Keywords: Dicipline; Employee Performance; Job Description.